2017
DOI: 10.1111/add.13651
|View full text |Cite
|
Sign up to set email alerts
|

Substance use outcomes of patients served by a large US implementation of Screening, Brief Intervention and Referral to Treatment (SBIRT)

Abstract: Aims To estimate changes in the substance use behaviors of patients who received services as part of the US Substance Abuse and Mental Health Services Administration's (SAMHSA) Screening, Brief Intervention and Referral to Treatment (SBIRT) grant program. Methods We use a pre-post design and performance monitoring data collected by SBIRT organizations. For a sample of 17 575 patients, we compare pre-SBIRT substance use with substance use 6 months after receipt of SBIRT services. SBIRT's correlation with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 35 publications
1
64
0
Order By: Relevance
“…Aldridge et al [27] took advantage of the extensive baseline, discharge and 6-month substance use outcome data collected by SAMHSA to re-evaluate the results of a prior study of the cohort 1 programs [28]. The results of the previous study were largely positive, but it did not employ appropriate statistical methods to assess patient improvements.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…Aldridge et al [27] took advantage of the extensive baseline, discharge and 6-month substance use outcome data collected by SAMHSA to re-evaluate the results of a prior study of the cohort 1 programs [28]. The results of the previous study were largely positive, but it did not employ appropriate statistical methods to assess patient improvements.…”
Section: Patient Outcomesmentioning
confidence: 99%
“…A summary
of findings concluded that after 6 months, the prevalence of alcohol use and heavy drinking was lower by 35.6% and 43.4%, respectively, which was statistically significant. As a result, this study provides data to support application of SBIRT to improve patient outcomes . SAMHSA also reports a 55% reduction in negative social consequences for those who receive care from SBIRT trained clinicians .…”
Section: Screening Brief Intervention and Referral To Treatmentmentioning
confidence: 72%
“…As a result, this study provides data to support application of SBIRT to improve patient outcomes. 10 SAMHSA also reports a 55% reduction in negative social consequences for those who receive care from SBIRT trained clinicians. 11 Finally, for every dollar spent on SBIRT implementation, approximately $4.30 is saved in future health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…program precluded the recruitment of control or comparison groups, the objective of the cross-site outcome evaluation was to confirm that the SBIRT models implemented by the SAMHSA programs yielded the changes in patient/client substance use behaviors that are suggested by the extensive clinical trial literature. Two papers in this Supplement present findings from the cross-site outcome evaluation: one focused upon pre-post changes in substance use associated with SBIRT services [27]; the other employed propensity score-matching to assess the incremental effect of BT relative to BI [28].…”
Section: Sbirt Cross-site Evaluationsmentioning
confidence: 99%